Cover Picture: Shaping Covalent Triazine Frameworks for the Hydrogenation of Carbon Dioxide to Formic Acid (ChemCatChem 13/2016). Issue 13 (6th July 2016) - Bavykina, Anastasiya V.; Rozhko, Elena; Goesten, Maarten G.; Wezendonk, Tim; Seoane, Beatriz; Kapteijn, Freek; Makkee, Michiel; Gascon, Jorge
Abstract : The Front Cover shows a formation of covalent triazine framework (CTF) based spheres using commercially available polyimide as a binder. In their Full Paper, A. V. Bavykina et al. present a facile one‐step method to shape CTFs into composite spheres with accessible porosity, high mechanical, and thermal stability. They used the fabricated spheres to host organometallic Ir III complex and obtained a catalyst, which is active and fully recyclable in the direct hydrogenation of carbon dioxide into formic acid. More information can be found in the Full Paper by A. V. Bavykina et al. onpage 2217 in Issue 13, 2016 (DOI:10.1002/cctc.201600419 ).